Motivation and compliance to type 2 diabetes mellitus diet - Deshita Rimadania; Eka Afrima Sari; Citra Windani Mambang Sari (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Type 2 Diabetes Mellitus (DM) is one of chronic diseases resulting from decreased insulin production and is characterized by an increase in glucose in the blood. Dietary adherence is one of the effective managements that can control blood sugar levels. This management requires supporting factors and one of them is motivation. This research aimed to describe the motivation and dietary compliance of patients with type 2 DM at the working area of Puskesmas Padalarang. This quantitative descriptive research used a cross-sectional approach. The samples were selected using proportional random sampling techniques. This study used the Treatment Self-Regulation Questionnaire (TSRQ) with the validity score 0.4821 and a diet adherence questionnaire with the validity score 0.4732. The results showed that the internal motivation of respondents was a good internal motivation with 33.3% and 66.7% had low motivation. Only 2.2% had good external motivation and almost all respondents had a low external motivation with 97.8%. Meanwhile, there were only 3.3% with a good level of adherence, 94.4% with a sufficient level of adherence and 2.2% had a poor level of diet adherence. Therefore, it is expected for Puskesmas to implement more motivational interviewing therapy to increase motivation and diet adherence in type 2 DM patients.